Achieving 5.9% elastic strain in kilograms of metallic glasses: Nanoscopic strain engineering goes macro. (July 2020) - Zhang, Junsong; Liu, Yinong; Yang, Hong; Ren, Yang; Cui, Lishan; Jiang, Daqiang; Wu, Zhigang; Ma, Zhiyuan; Guo, Fangmin; Bakhtiari, Sam; Motazedian, Fakhrodin; Li, Ju
Graphical abstract: Abstract: The ideal elastic limit is the upper bound of the achievable strength and elastic strain of solids. However, the elastic strains that bulk materials can sustain are usually below 2%, due to the localization of inelastic deformations at the lattice scale. In this study, we achieved >5% elastic strain in bulk quantity of metallic glass, by exploiting the more uniform and smaller-magnitude atomic-scale lattice strains of martensitic transformation as a loading medium in a bulk metallic nanocomposite. The self-limiting nature of martensitic transformation helps to prevent lattice strain transfer that leads to the localization of deformation and damage. This lattice strain egalitarian strategy enables bulk metallic materials in kilogram-quantity to achieve near-ideal elastic limit. This concept is verified in a model in situ bulk amorphous (TiNiFe)-nanocrystalline (TiNi(Fe)) composite, in which the TiNiFe amorphous matrix exhibits a maximum tensile elastic strain of ∼5.9%, which approaches its theoretical elastic limit. As a result, the model bulk composite possesses a large recoverable strain of ∼7%, a maximum tensile strength of above 2 GPa, and a large elastic resilience of ∼79.4 MJ/m 3 . The recoverable strain and elastic resilience are unmatched by known high strength bulk metallic materials. This design concept opens new opportunities for the development of high-performance bulk materials and elastic strain engineering of the physiochemical properties of glasses.